2018
DOI: 10.2147/idr.s151271
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivities of coagulase-negative staphylococci and <em>Staphylococcus aureus</em> in hip and knee periprosthetic joint infections: does this differ if patients meet the International Consensus Meeting Criteria?

Abstract: IntroductionCoagulase-negative staphylococci (CoNS) are the main pathogens responsible for prosthetic joint infections (PJIs). As normal inhabitants of human skin, it is often difficult to define if they are contaminants, or if they have an active role in initiating infection. This study aims to evaluate differences in CoNS organisms (Staphylococcus hominis, Staphylococcus capitis, Staphylococcus haemolyticus, Staphylococcus warneri) and Staphylococcus aureus in terms of isolation rate and antimicrobial suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Several studies have identified S. epidermidis as the most commonly isolated CoNS. 22 , 25 – 29 In contrast, some studies have suggested S. capitis 30 and S. hemolyticus 10 , 31 , 32 as the most common CoNS. S. epidermidis is the most common commensal of our skin and mucosa, and contamination through the devices during medical procedures are very common.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified S. epidermidis as the most commonly isolated CoNS. 22 , 25 – 29 In contrast, some studies have suggested S. capitis 30 and S. hemolyticus 10 , 31 , 32 as the most common CoNS. S. epidermidis is the most common commensal of our skin and mucosa, and contamination through the devices during medical procedures are very common.…”
Section: Discussionmentioning
confidence: 99%
“…According to the performed systematic search, only two studies have assessed NSAID activity against relevant pathogenic coagulase-negative staphylococci in the last 5 years ( Pereira et al, 2018 ; Abidi et al, 2019 ). These organisms are the most common causes of healthcare-associated biofilm-related infections, like catheter-related bloodstream infections and prosthetic joint infections ( De Vecchi et al, 2018 ; Hebeisen et al, 2019 ). Species like S. epidermidis , Staphylococcus haemolyticus , Staphylococcus hominis , are also important biofilm-forming microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of devices such as intravascular catheters as well as the increase in invasive manipulation in immunosuppressed patients, have been recognized as one of the important factors associated with nosocomial infections caused by bacteria (Supré et al, 2011). The frequency of CoNS infection has been increasing mainly due to bacteremia, catheter-related infections, endocarditis, and urinary tract infections; moreover, resistance to antibiotics, especially vancomycin, is a serious problem, as bacteria demonstrating severe resistance have been identified (Koksal et al, 2009;De Vecchi et al, 2018). A 2013 study for Azih et al, has reported that 105 CoNS were isolated from 79 clinical specimens, such as discharge from wounds, urine, and male genital infections, which could cause secondary infections, such as sepsis (Azih and Enabulele, 2013).…”
Section: Importance Of Consmentioning
confidence: 99%
“…Therefore, management of established PJI requires a combination of pathogen-specific antibiotics and surgical intervention (De Vecchi et al, 2018).…”
Section: Cons In Periprosthetic Joint Infection (Pji)mentioning
confidence: 99%
See 1 more Smart Citation